THE INFLUENCE OF STORE ATMOSPHERE, EXTERNAL STIMULI, PRODUCT ATTRIBUTES ON IMPULSE BUYING - Rohmad Prio Santoso; Winaika Irawati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This study aims to analyse the influence of store atmosphere, external stimuli, and product attributes on impulse buying behaviour in consumers who shop at Kediri Town Square supermarkets. Impulse buying is a purchase that occurs spontaneously without prior planning, often triggered by external factors and in-store situations. Store atmosphere includes elements such as lighting, music, layout, and aroma that can create a comfortable and attractive shopping atmosphere, thus encouraging consumers to make impulse purchases. External stimuli such as promotions, advertisements, and product displays also play a significant role in influencing spontaneous purchase decisions. In addition, product attributes including product design, quality, packaging and price can be the main attraction for consumers, encouraging them to buy products without thinking. This study uses a quantitative method with a survey approach with a sample size of 35 respondents, to collect data obtained from consumers who shop at Kediri Town Square supermarkets in Kediri City, and data analysis techniques are carried out using (SEM) structural equation modelling with the help of smart PLS software. The results showed that the three variables have a significant influence on impulse buying behaviour in consumers, with store atmosphere and external stimuli having a greater impact than product attributes. The findings provide insights for business practitioners regarding the importance of managing these elements to increase sales through impulse purchases.